Glabridin inhibits migration and invasion by transcriptional inhibition of matrix metalloproteinase 9 through modulation of NF‐κB and AP‐1 activity in human liver cancer cells. (June 2014) - Hsieh, Ming‐Ju; Lin, Chiao‐Wen; Yang, Shun‐Fa; Chen, Mu‐Kuan; Chiou, Hui‐Ling
<x xml:space="preserve">Abstract</x> Background and Purpose High mortality and morbidity rates for hepatocellular carcinoma in Taiwan primarily result from uncontrolled tumour metastasis. Glabridin, a prenylated isoflavonoid of licorice (Glycyrrhiza glabra) roots, is associated with a wide range of biological properties, such as regulation of energy metabolism, oestrogenic, neuroprotective, anti‐osteoporotic and skin whitening. However, the effect of glabridin on the metastasis of tumour cells has not been clarified. Experimental Approach A wound healing model and Boyden chamber assays in vitro were used to determine the effects of glabridin on the migration and invasion of human hepatocellular carcinoma (HHC) cells. Western blot analysis, gelatin zymography, real‐time PCR and promoter assays were used to evaluate the inhibitory effects of glabridin on matrix metalloproteinase 9 (MMP9) expression in these cells. Key Results Glabridin significantly inhibited migration/invasion capacities of HCC cells, Huh7 and Sk‐Hep‐1, cell lines that have low cytotoxicity in vitro, even at high concentrations. Western blot analysis and gelatin zymography showed that glabridin inhibited the expression, activities and protein levels of MMP9 and the phosphorylation of ERK1/2 and JNK1/2. These inhibitory effects were associated with an up‐regulation of tissue inhibitor of metalloproteinase‐1 and a down‐regulation of the transcription factors NF‐κB and activator protein 1 signalling pathways. Finally, the administration of glabridin effectively suppressed the tumour formation in the hepatoma xenograft model in vivo. Conclusion and Implications Glabridin inhibited the invasion of human HCC cells and may have potential as a chemopreventive agent against liver cancer metastasis.